Exploring Best Practices and Tensions in Immigrant-Led Community-Based Social Service Planning Models for Immigrant and Refugee Communities - Sandeep K. Dhillon; Stefanie Machado; Ryan Wai Shing Lai 黎韋成; Kari Grain (Journal of Community Engagement and Scholarship)
Canada’s immigrant resettlement model places non-governmental community-based agencies at the front of service delivery, with program funding often provided federally through Immigration, Refugees and Citizenship Canada (IRCC). Historically, “top-down” approaches supporting immigrants have been planned and employed by governments and corporations to institute exclusionary policies and regulations. In contrast, “bottom-up” approaches, including grassroots community-based initiatives, have addressed localized issues in newcomer and refugee experiences. While current resettlement models rely on grassroots and community-based programs to deliver needed services, there are nonetheless few community-based planning models for social services that are led or informed by immigrant community members, including newcomers and refugees. This article explores immigrant-led, community-based social service planning models to inform and strengthen integration support for newcomers and refugees in British Columbia, Canada. Drawing from community-engaged principles, this article presents findings from a secondary analysis conducted by a team of researchers from Simon Fraser University with the collaboration of community partners. Based on the guidance of community partners in the immigrant and refugee settlement sector who are leading the direction of the project, the information presented in this paper focuses on community-based initiatives related to four social determinants of health: housing, employment, gender identity, and immigration status. Findings are based on immigrant integration models from case studies and published research across the globe and elucidate critical themes in terms of promising practices, tensions and challenges, and recommendations for effective service delivery models in immigrant integration organizations.